Analysis of chip serration phenomenon in side milling of ultrahigh-strength steel 30CrMnSiNi2A. Issue 1 (January 2017) - Niu, Qiulin; Li, Pengnan; Chen, Ming; Ming, Weiwei; Tang, Siwen
Abstract Ultrahigh-strength steel 30CrMnSiNi2A is a significant bearing material and is also a typical different-to-cut material. The main goal of this work is to analyze the serration phenomenon of chips in side milling 30CrMnSiNi2A. A series of experiments were conducted on a milling machine to study the effect of cutting speed and feed per tooth on the chip formation. The chip morphology and the formation of serrated chip were analyzed. The degree of serration of chips was evaluated with both sawtooth height ratioG s and tooth pitchP c . This study calculated the serration frequency and achieved the mathematical expression for the serration frequency with the cutting speed. The analysis results in the formation of the chip showed that, when increasing feed per tooth in side milling 30CrMnSiNi2A steel, the serrated chip was periodically broken.